Analisis Perbandingan Gametogenesis pada Hewan Vertebrata dan Invertebrata - Nafasya Rahmandini; Na’illah Ega Sivana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
In mammals, the reproductive process involves fertilization between male and female gametes that produce embryos. Gametogenesis, which includes spermatogenesis and oogenesis, is the stage of formation and maturation of gamete cells through mitosis and meiosis division. The purpose of this study is to understand the differences and similarities in the process of gametogenesis in vertebrate and invertebrate animal groups. This study uses a literature study method in obtaining its data. Although there are variations in structure and mechanism, the process of gametogenesis in vertebrates and invertebrates has similar basic principles. Environmental factors such as temperature also play an important role in influencing spermatogenic activity and reproductive behavior in both groups of animals. The similarities in the basic process indicate that gametogenesis is an evolutionarily conservative mechanism, while specific variations reflect adaptation to the reproductive needs of each species.